2005
DOI: 10.1002/cncr.21431
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact and frequency of anatomic pathology errors in cancer diagnoses

Abstract: BACKGROUND.To the authors' knowledge, the frequency and clinical impact of errors in the anatomic pathology diagnosis of cancer have been poorly characterized to date. METHODS.The authors examined errors in patients who underwent anatomic pathology tests to determine the presence or absence of cancer or precancerous lesions in four hospitals. They analyzed 1 year of retrospective errors detected through a standardized cytologic-histologic correlation process (in which patient same-site cytologic and histologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
140
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(143 citation statements)
references
References 35 publications
3
140
0
Order By: Relevance
“…7 Major disagreement rates show wide variability, ranging from 0.3% to 10%, depending on many factors such as the tissue type, the type of referral (physician requested or routine transfer), and the institution. [8][9][10][11][12][13][14][15][16][17] We are not aware of any studies that have explored the interactions between these 2 types of bias in FNAB DTA studies. In addition and importantly, verification bias and classification bias may interact in unpredictable ways so that it is difficult to estimate the total bias based on the estimated bias due to each component.…”
Section: Introductionmentioning
confidence: 99%
“…7 Major disagreement rates show wide variability, ranging from 0.3% to 10%, depending on many factors such as the tissue type, the type of referral (physician requested or routine transfer), and the institution. [8][9][10][11][12][13][14][15][16][17] We are not aware of any studies that have explored the interactions between these 2 types of bias in FNAB DTA studies. In addition and importantly, verification bias and classification bias may interact in unpredictable ways so that it is difficult to estimate the total bias based on the estimated bias due to each component.…”
Section: Introductionmentioning
confidence: 99%
“…6 Another study has shown that the frequency of errors in cancer diagnosis are institution-dependent and may occur in up to 11.8% of all cytologic-histologic specimen pairs. 7 In addition to diagnostic discrepancies, standard pathological review at the biobank may also yield incidental findings previously unobserved at the collection site. In the context of biobanking, a "pathological incidental finding" is considered to be any clinically relevant information about a biospecimen discovered during review by the biobank that was not noted at the biospecimen collection site.…”
mentioning
confidence: 99%
“…Recent examples abound, 34,[46][47][48][49][50][51][52][53][54][55][56] regardless of whether the operative terms are 'interobserver variation' or outright 'error'. [57][58][59] We thus encounter a fundamental challenge in the use of morphological data in EBM.…”
Section: Anatomic Pathology As a 'Gold Standard'mentioning
confidence: 99%